THE RELEVANCE OF THE CONCEPT OF UMMATAN WASATHAN WITH PANCASILAIS: A CRITICAL REVIEW OF AL-MISHBAH'S TAFSIR - Hulaimi Azhari (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
The birth of this paper is motivated by the phenomenon of many people interpreting the meaning of the wasathan ummah without being based on the terms and conditions of being a commentator. The interpretation of the Qur'an always experiences a shift in tandem with the changing times and changing times. To understand the eating of was Nathan Sumatran referred to in QS Al-Baqarah 143, not all Muslims understand its meaning but only some people who have certain knowledge (Mufassir). In determining the explicit and implicit meaning of the word summation was then, experts apply various kinds of scientific discourse, such as interpretation and ta'wil which then find the findings of the two methods. Besides that, internalizing the word summation was then with the concept of Pancasila is the subject of this paper.Keywords: Ummatan Wasathan, Tafsir, Ta'wil, Pancasila.